Assessment of Resident Physician Program: A Case Study of Mazandaran - Ghasem Abedi; Roya Malekzadeh; Afshin Amirkhanlou (Journal of Mazandaran University of Medical Sciences, 2018)
Background and purpose: In order to increase the accountability of hospitals and ensuring proper medical treatments at any time of the day, physicians residing in non-administrative hours have active physical presence in the hospital and perform the diagnostic and therapeutic measures required. The purpose of this study was to assess the implementation of resident physician program in Mazandaran province, Iran. Materials and methods: A qualitative study was carried out in which the participants included 27 individuals from university authorities, hospital managers, and specialists. Data was collected by semi-structured interviews using purposeful and snowball methods and continued until data saturation. Then, transcription of interview data was done to determine the meaning units, coding, classification based on similarity and proportion, and identifying themes using content analysis. Results: According to the framework of the resident physician program, 13 primary themes and 47 secondary themes were extracted. This program improved the centers’ responses, indicators, and processes. But some themes such as finance, infrastructures, monitoring, implementation of the program, and payments to doctors were found as challenging issues requiring more attention. Conclusion: Considering the opportunities and threats, and the strengths and weaknesses of the resident physicians program, current findings could provide managers and healthcare authorities with a more comprehensive approach to the present situation.